I need to solve for C: V=C- C-S N
.................................L
The periods don't go in the equation, it was the only way I could get the L under C-S
The steps I did were:
LV=LC-N(C-S)
LV=LC-NC+NS
LV-NS=LC-NC
LV-NS=C(L-N)
I came up with C=LV-NS
......................L-N
Not sure if that is right, I would also like to know what this is the formula for. thanks
.................................L
The periods don't go in the equation, it was the only way I could get the L under C-S
The steps I did were:
LV=LC-N(C-S)
LV=LC-NC+NS
LV-NS=LC-NC
LV-NS=C(L-N)
I came up with C=LV-NS
......................L-N
Not sure if that is right, I would also like to know what this is the formula for. thanks